Inadequate Dosage May Lead to the Recurrence of Postoperative Pulmonary Hypertension in Patients With Congenital Heart Disease - Li, Xinmei; Li, Te (Frontiers in Pharmacology, 2021)
Background: Pulmonary arterial hypertension (PAH) associated with congenital heart disease (PAH-CHD) occurs predominantly among patients with uncorrected congenital heart disease (CHD). It is an intractable problem to control PAH continuously and stably after an operation. Methods: 1) OPLS-DA combined with S-plot was used to retrospectively analyze the results of preoperative and postoperative PAH and 39 biochemical indicators of 235 patients admitted to Fuwai Yunnan Cardiovascular Hospital from January 2019 to December 2020. 2) Combined with Meta-analysis, the recurrence in postoperative PAH was analyzed in terms of operation factors, doses administered, and age factors. Results: 1) 4 indicators (PAH, RBC, HGB, and CO2) that reflect the prognosis of patients had been found by OPLS-DA combined with S-plot. 2) The recurrence rate of postoperative PAH was 37.02%. The comprehensive therapeutic effect of interventional closure was better than that of surgical operation. PAH was not significantly higher again in patients who received either the instruction dose or the literature dose. Postoperative combination therapy (bosentan and sildenafil) was more effective than bosentan alone. Recovery after treatment was better in infants than in the other four age groups. Conclusion: OPLS-DA combined with S-plot was used for the first time to analyze clinical examination data. In this study, this method proved to be a feasible method for analyzing clinical data We recommend interventional closure as the first choice for patients with PAH-CHD. For postoperative oral therapy, we recommend the combination therapy (bosentan with sildenafil). To prevent the recurrence, the dose should be strictly prescribed according to the instructions, literature, or body surface area converted. Moreover, we recommend treatment at a young age in these patients.